The Effect of Distance Teaching Experiences on Educators' Attitudes toward Distance Education for Preschoolers - Alexander Veraksa; Apollinaria Chursina; Margarita Gavrilova (MDPI AG, 2021)
The aim of the study was to explore and highlight the challenges and benefits of distance education that educators found in their practice of online teaching with preschool children during the first wave of the pandemic. An electronic questionnaire was used to collect teachers' perceptions of (1) their own success in facilitating online sessions; (2) attitudes towards online sessions among teachers with and without experience; (3) factors that, according to teachers with and without experience, determine the effectiveness of online sessions; (4) effectiveness of online sessions for individual mental development goals among teachers with and without such experience. A total of 623 educators participated in the study. Online sessions were of particular benefit to educators who had experience of working remotely with preschool children during the first wave of the pandemic. The results of this study indicate that the capacity of the children and the effectiveness of the online sessions themselves exceeded teachers' expectations in many ways.